Canine ehrlichiosis: clinical, hematological, serological and molecular aspects - Andréa Cristina Higa Nakaghi (Ciência Rural, 2008)
The aim of the present study was to compare thedirect detection methods of Ehrlichia canis (blood smears andnested PCR), serological tests (Dot-ELISA andImmunofluorescent Antibody Test - IFAT), and demonstratethe most suitable test for the diagnosis of different stages ofinfection. Blood samples and clinical data were collected from30 dogs examined at the Veterinary Teaching Hospital, UNESP,Jaboticabal, SP, Brazil. The clinical signs most frequentlyobserved were apathy, anorexia, pale mucous membrane, fever,lymphadenopathy, splenomegaly, hemorrhages and uveitis.Evaluating the humoral immune response, 63.3% of the serawere IFAT positive, while 70% were Dot-ELISA positive. BynestedPCR 53.3% of the samples were positive. Comparingthese techniques it was concluded that serology and nPCR arethe most suitable tests to confirm the diagnosis of canineehrlichiosis, however it should be always treated as acomplementary data to clinical and hematological evaluation.Serology has an important role in the subclinical and in thechronic phase, nPCR is recommended in the acute stage, and,especially, to identify the ehrlichia specie.